Management Strategic on Formulating and Socializing the Vision and Mission at Islamic College Putra Galuh Ciamis - Hidayat, Yusuf; Herniawati, Ani; Hidayat, Ara (CV. Tripe Konsultan, 2025)
Vision and mission are the main parts which should be formulated, socialized, understood together, and implemented collectively and consistently to achieve the goals of an institution. This study aims to identify the vision and mission formulated and socialized at Islamic college Putra Galuh Ciamis. In this study, the researchers used qualitative approach under phenomenological method. The results of the study showed that the vision and mission were formulated and socialized within 6 stages: forming a team to develop the vision and mission of Islamic college Putra Galuh Ciamis; preparing a draft of the vision and mission plan for Islamic college Putra Galuh Ciamis; revising the draft that has been designed; creating harmony between the vision, mission, goals, and programs conducted at Islamic college Putra Galuh Ciamis; making decision by listening the inputs from the lecturers, the students, the users and other stakeholders in a forum taken place at Islamic college Putra Galuh Ciamis; and socializing the vision, mission, goals and programs to the whole academic community at Islamic college Putra Galuh Ciamis. In addition, the barrier factors at which vision and mission are hardly known and understood by the whole stakeholders, including: lack of awareness of each academic community to memorize well the vision and mission that had been socialized; the socialization of the vision and mission has not been conducted sustainably; and the vision and mission that have been socialized have not been posted in every room, so that the whole students have not read them. The new findings as the novelty of the present study is in the form of the supporting factors as the solutions to overcome the barrier factors. Those supporting factors include: the setting of banners containing the vision and mission of Islamic college Putra Galuh Ciamis were taken place in the leaders’ rooms, lecturers’ room, and administration room; the vision and mission are written in the student's thesis writing guidebook; and the vision and mission were also posted in the website of Islamic college Putra Galuh Ciamis, so that it can be easily accessed by online.